Association Between Nonmotor Symptoms and Nonadherence to Medication in Parkinson's Disease - Mendorf, Sarah; Witte, Otto W.; Zipprich, Hannah; Prell, Tino (Frontiers in Neurology, 2020)
Background:Non-adherence to medication is a common and serious issue in the treatment of patients with Parkinson’s disease (PD). Among others, distinct non-motor symptoms (NMS) were found to be associated with non-adherence in PD. Here, we aimed to confirm the association between NMS and adherence. Methods: In this observational study, the following data were collected:sociodemographic data, the German versions of the Movement Disorder Society-sponsored revision of the unified Parkinson’s disease rating scale for motor function (MDS-UPDRSIII), Hoehn&Yahr (H&Y) stage, levodopa equivalent daily dose (LEDD), Becks depression inventory II (BDI-II), non-motor symptoms questionnaire (NMSQ) and the Stendal adherence to medication score (SAMS). Results: The final sample included 137 people with PD (54[39.4%] female) with a mean age of 71.3±8.2 years. According to SAMS, 10.9% of patients were fully adherent, 73% moderately non-adherent and 16.1% showed clinically significant non-adherence. Non-adherence was associated with LEDD, BDI-II, education level, MDS-UPDRS III and the NMSQ. The number of NMS was higher in non-adherent patients than in adherent patients. In the multiple stepwise regression analysis, the items 5 (constipation), 17 (anxiety) and 21 (falls) predicted non-adherence to medication. These NMSQ items also remained significant predictors for SAMS after correction for LEDD, MDS-UPDRS III, BDI-II, age, education level, gender and disease duration. Conclusion: Our study, confirms the association between NMS burden and non-adherence in PD. However, in contrast to other clinical factors, the relevance of NMSQ in terms of non-adherence is low. Studies with larger sample sizes are necessary to explore the impact of distinct NMS on adherence.